Anaerobic digestion of wheat straw and rape oil cake in a two-stage solid-state system. (October 2019) - Pohl, Marcel; Sánchez-Sánchez, Maria; Mumme, Jan
Abstract: In this study, the anaerobic co-digestion of two abundantly available agricultural waste streams, rape oil cake and wheat straw, was investigated using the upflow anaerobic solid-state (UASS) process. The experiment was carried out in two identically constructed UASS systems operated for 154 days at 37 °C and 55 °C, respectively, and at organic loading rates (OLR) of 2.5, 3.5 and 4.5 gVS L −1 d −1 . Additionally, the influence of the carbon-to-nitrogen ratio of the substrate on the process was examined. It was found that the process performance was higher by 18% at thermophilic temperature and an OLR of 2.5 gVS L −1 d −1 . However, with rising OLRs, this advantage in degradation efficiency diminishes down to +2.2% at the highest OLR observed. Although rape oil cake increased methane yields as compared to straw as sole substrate, no synergies were observed. At both temperature levels, an accumulation of volatile fatty acids (VFAs) and ammonium was observed. However, no noticeable inhibition occurred during the course of the experiments which suggests increased tolerance through microbial adaptation. Highlights: Rape oil cake and wheat straw pose an effective mixture for co-fermentation. The two-phase solid-state system is capable of digesting nitrogen-rich substrates. Thermophilic temperature showed higher degradation rates than mesophilic. Thermophilic operations were prone to ammonia inhibition and clogging. Addition of rape oil cake increased methane yields compared to sole straw.